Affective damage from teachers’ written corrective feedback - Gartika Pandu Bhuana; Ula Nisa El Fauziah (EduLite: Journal of English Education, Literature and Culture, 2021)
Several studies believe that providing feedback on a students’ writing task offers several benefits. However, giving excessive corrections on students’ mistakes can have a negative impact on the students’ feeling. This study aims to investigate English Foreign Language students’ emotional response to the teachers’ written corrective feedback. A qualitative method was applied. The participants were 72 third grade students at an institution in Cimahi. To collect the data, a five-point Likert scale questionnaire and a semi-structured interview were applied. The results revealed that the teachers’ written corrective feedback had negative impact to the students’ feelings, especially for the students who had mid and low proficiency level in writing. It even led to the students’ demotivation. This indicates that the teachers have to consider several things before they give some written feedback as it can affect the students’ attitude in a negative way.